Food access, domestic environments, and dietary quality of low-middle income Chilean children during the COVID-19 pandemic - Pemjean, Isabel; Mediano, Fernanda; Ferrer, Pedro; Garmendia, María Luisa; Corvalán, Camila (Frontiers in Public Health, 2023)
Introduction: Food access is associated with dietary quality, however, people living in similar physical environments can have different food access profiles. Domestic environments may also influence how food access relates to dietary quality. We studied food access profiles of 999 low-middle-income Chilean families with children during the Covid-19 lockdown and how these profiles relate to dietary quality. Secondarily, we also explore the role of the domestic environment on this relationship. Materials and methods: Participants of two longitudinal studies conducted in the Southeast of Santiago, Chile answered online surveys at the beginning and end of the Covid-19 lockdown. Food access profiles were developed by Latent Class Analysis considering food outlets and government food transfers. Children's dietary quality was estimated by self-reported compliance with the Chilean Dietary Guidelines (DGA) and daily ultra-processed food (UPF) consumption. Logistic and linear regressions were used to assess the associations between food access profiles and dietary quality. Domestic environment data (i.e. sex of the person who buys foods and cooks, meal frequency, cooking skills, etc.) were incorporated into the models to assess their influence on the relationship between food access and dietary quality. Results: We identified three food access profiles: Classic (70.2%), Multiple (17.9%), and Supermarket-Restaurant (11.9%); being female head of household more frequent in the Multiple profile and being of higher income or education, in the Supermarket-Restaurant profile. On average, children presented poor dietary quality, with a high daily UPFs consumption (median=4.4; IQR:3), and low compliance with national DGA recommendations (median=1.2; IQR:2). Except for the fish recommendation (OR=1.77, 95% CI:1.00-3.12; p:0.048 for Supermarket-Restaurant profile), the food access profiles were poorly associated with children's dietary quality. However, further analyses showed that domestic environment variables related to routine and time-use, influenced the association between food access profiles and dietary quality. Conclusions: In a sample of low-middle income Chilean families we identified three food access profiles that presented a socioeconomic gradient; however, these profiles did not significantly explain children's dietary quality. Studies diving deeper into household dynamics might give us some clues on intra-household behavior and roles that could be influencing how food access relates to dietary quality.